2021
DOI: 10.1007/s10750-021-04522-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate particle size on burrowing of the juvenile freshwater pearl mussel Margaritifera margaritifera

Abstract: Juveniles of the endangered freshwater pearl mussel (FPM, Margaritifera margaritifera) live burrowed in stream substrate for the first years of their life. Fine sediments block water exchange within substrate and may cause juvenile mortality and recruitment failure. To better understand the connection between success of juvenile FPM and substrate particle size, it would be important to understand behavioural responses of FPM to varying substrate sizes at this critical life stage. We placed newly detached FPM j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…However, the tightness of the small grain size substrate will cause the shear strength of the substrate to increase, which has a negative impact on the burrowing of shellfish [ 3 , 42 ]. However, the present study found that the burrowing time of M. meretrix in fine sand with a higher shear strength was the shortest, which may be because M. meretrix ’s burrowing was carried out using both morphological and behavioral effects [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the tightness of the small grain size substrate will cause the shear strength of the substrate to increase, which has a negative impact on the burrowing of shellfish [ 3 , 42 ]. However, the present study found that the burrowing time of M. meretrix in fine sand with a higher shear strength was the shortest, which may be because M. meretrix ’s burrowing was carried out using both morphological and behavioral effects [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the natural environment, less fertile M. meretrix are more likely to exhibit mobile behavior, as a poor nutritional status means that the current habitat may lack food, or have a high predation pressure, unsuitable temperature, or salinity, and they need to migrate to find more suitable habitat [ 54 ]. Therefore, the movement behavior of M. meretrix can be regarded as an effective survival strategy for individuals under external environmental stress, and movement behavior can help them to avoid the harsh survival environment and to meet the survival needs of their different life stages [ 15 , 42 ]. In this study, M. meretrix showed a high percentage of movement in coarse sandy substrate, which may mean that coarse sandy substrate is not a suitable habitat for M. meretrix .…”
Section: Discussionmentioning
confidence: 99%
“…Finer substrates, such as silt, may contain more organic matter as a food source for filter-feeding mussels (Lara & Parada, 2009), although silt is also considered to be detrimental to feeding and respiratory activity in mussels (Roper & Hickey, 1995;Brim Box & Mossa, 1999). A more likely explanation for a preference for finer substrates may be that they enhance burrowing efficiency (Lewis & Riebel, 1984;Morales et al, 2006;Poznańska-Kakareko et al, 2021; although see Hyvärinen et al, 2021 for a contrary finding with juvenile mussels). Burrowing may provide protection against drought (Amyot & Downing, 1997;Gough et al, 2012), which would be an important adaptation in regions with non-perennial rivers, such as south-western Australia, where river drying is a regular annual occurrence.…”
Section: Habitat Preferencementioning
confidence: 99%
“…Conditions that are near anoxic have caused acute mortality in juvenile unionids (Dimock & Wright, 1993), and Bílý et al (2020) observed that decreased dissolved oxygen within the test substrate was associated with a low survival rate of juvenile FPMs. In addition, fine substrate—which leads to low dissolved oxygen conditions (reviewed by Ryan, 1991)—has been associated both with low recruitment of FPMs (Geist & Auerswald, 2007) and surfacing behaviour in juvenile FPMs (Hyvärinen et al, 2021). Thus, both correlative evidence from field studies and the results of laboratory experiments indicate that juvenile freshwater mussels are sensitive to low dissolved oxygen, but to our knowledge the effect of low oxygen concentration on the survival or viability of FPM juveniles has not been studied experimentally.…”
Section: Introductionmentioning
confidence: 99%